“All things are double”: Eudora Welty’s Prismatic view - Lima, Maria Antónia (2014)
This essay argues that Eudora Welty’s vision was influenced by the American Gothic tradition, with its emphasis on doubleness and mystery. Indeed, not only in several interviews conceded throughout her career but also in her essays and in her fictional writing, did Welty refuse to indulge into conclusive generalizations or to moralize her readers. Thus, she revealed an extraordinary capacity to probe the constitutive ambivalence of situations and characters, and to allude to the flux at the heart of life.